Development of a HPLC-UV Method for the Separation and Quantification of Hesperidin, Neohesperidin, Neohesperidin Dihydrochalcone and Hesperetin. Issue 10 (19th May 2023) - Chen, Lin; Zhu, Siming; Wang, Chunqing; Chen, Liang
Abstract: An analysis method was developed for the separation and quantification of hesperidin, neohesperidin, neohesperidin dihydrochalcone and hesperetin by using HPLC-UV. Single factor experiments and Box-Behnken Designs were used to optimize separation of four flavonoids, in which a gradient elution method was adopted with 99% acetonitrile and 0.1% formic acid as mobile phases at a flow rate of 0.9 mL/min. A C18 column was used with a column temperature of 35 °C. LODs and LOQs were below 0.84 µg/mL and 2.84 µg/mL, respectively. Linearity with good correlation coefficients ( r > 0.99, n = 5) was attained, recovery rate of four flavonoids ranged from 88% to 130%, the RSD indicating results precision for analyzing hesperidin, neohesperidin, neohesperidin dihydrochalcone and hesperetin ranged from 1.2% to 4.6%. Finally, the present method could be successfully applied to identify and quantify hesperidin, neohesperidin and hesperetin in Fructus Aurantii Immaturus and Pericarpium Citri Reticulatae . Graphical Abstract: UF0001